Penggunaan Internet Sebagai Media Sumber Literatur oleh Mahasiswa Program Magister: Pendekatan Model TAM (Technology Acceptance Model) yang Dimodifikasi - Sarasmitha, Citra; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2013)
The aim of this study is to investigate the determinants of internet usage as a media source literature by magister program students. This study employed a technology acceptance model (TAM) by Davis (1989) with modified for predicting. Data was collected from 181 magister program students from accounting department of Brawijaya University with survey method. Data was analyzed by Partial Least Square (PLS) software. The result shows that perceived ease of use, perceived internet content, and openness personalityhave positive significant influences to internet usage. Whereas perceived usefulness has not significant influences to internet usage. The implication of this study is relevant to lecturer and internet provider for considering about perception students at ease of use and quality information in internet. Despite this, lecturersshould know about personality students have a direct impact to internet usage. Â  Keywords: Technology Acceptance Model (TAM), perceived usefulness, perceived ease of use, perceived internet content, openness personality, internet usage, media source literature.